1994
DOI: 10.3168/jds.s0022-0302(94)77009-0
|View full text |Cite
|
Sign up to set email alerts
|

Winter Evaluation of a Postmilking Powdered Teat Dip

Abstract: A powdered teat dip designed for winter usage was evaluated for bacteriological efficacy and teat conditioning qualities. A positive control, natural exposure field trial was conducted for 3 mo on 509 lactating cows. Two sets of cows, primiparous and multiparous, were used. The trial compared efficacy of a powdered teat dip with a teat dip of 1% iodine plus 10% glycerin. Bacteriological efficacy among primiparous cows was equivalent for all major mastitis pathogens, environmental pathogens, and streptococci ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 4 publications
2
29
0
Order By: Relevance
“…Teat skin score (TSS) and teat end score (TES) were evaluated weekly on quarter level for all 40 cows based on the scoring system developed at the University of Vermont (Goldberg et al, 1994) (Table 2). Teat condition was scored five times before and eight times after AMS initiation, giving 2080 expected scores per response variable.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teat skin score (TSS) and teat end score (TES) were evaluated weekly on quarter level for all 40 cows based on the scoring system developed at the University of Vermont (Goldberg et al, 1994) (Table 2). Teat condition was scored five times before and eight times after AMS initiation, giving 2080 expected scores per response variable.…”
Section: Data Collectionmentioning
confidence: 99%
“…Teat end callosity increases the incidence of clinical mastitis (Neijenhuis et al, 2001b), and teat end condi-tion is associated with the occurrence of intramammary Staphylococcus aureus infections (Goldberg et al, 1994;Zadoks et al, 2001). It is, therefore, of paramount importance to preserve the best teat skin and teat end condition in the dairy herd, whether the cows are milked conventionally or automatically.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of teat end and teat skin condition in dipped and control teats were scored immediately before the trial was initiated and at the conclusion of the trial to determine any effects of the teat dip products on the condition of teat ends and lateral teat skin. The teats were given a score of 1 to 5 using visual and tactile observation (Goldberg et al, 1994;Neijenhuis et al, 2004). See Table 1 for a description of the ordinal scale and results of the scoring.…”
Section: Streptococcus Agalactiae (Mcdonald 44) Culturesmentioning
confidence: 99%
“…Characteristics of teat skin surfaces and teat ends for both groups of cows were scored immediately before the trial, weekly during the trial, and at the conclusion of the trial, to determine possible effects of the germicidal solutions on teat skin condition. Condition scores for teat skin and teat ends were characterized according to the criteria established by Goldberg et al (1994) by a single technician not informed as to the allocation of treatments. According to the criteria (Goldberg et al, 1994), a score of 1 to either teat end or teat skin indicated that the epidermis had no visual damage; a score of 5 to either site reflected severely damaged epidermis.…”
mentioning
confidence: 99%
“…Condition scores for teat skin and teat ends were characterized according to the criteria established by Goldberg et al (1994) by a single technician not informed as to the allocation of treatments. According to the criteria (Goldberg et al, 1994), a score of 1 to either teat end or teat skin indicated that the epidermis had no visual damage; a score of 5 to either site reflected severely damaged epidermis. To test differences in teat skin conditions between treated and control teats, a mixed model was constructed (SAS Institute, 1994).…”
mentioning
confidence: 99%